Peri-Intubation Cardiac Arrest in the Pediatric Emergency Department: A Novel System of Care. Issue 6 (November 2020) - Hoehn, Erin F.; Dean, Preston; Lautz, Andrew J.; Frey, Mary; Cabrera-Thurman, Mary K.; Geis, Gary L.; Stalets, Erika; Zackoff, Matthew; Pham, Tena; Maxwell, Andrea; Vukovic, Adam; Kerrey, Benjamin T.
Abstract : Introduction: Patients with physiologic disorders, such as hypoxemia or hypotension, are at high risk of peri-intubation cardiac arrest. Standardization improves emergency tracheal intubation safety, but no published reports describe initiatives to reduce the risk of cardiac arrest. This initiative aims to improve the care of children at risk of peri-intubation cardiac arrest in a pediatric emergency department (PED). We specifically aimed to increase the number of patients between those with peri-intubation cardiac arrest by 50%, from a baseline of 11–16, over 12-months. Methods: Our multidisciplinary team outlined a theory of improvement and designed interventions aimed at key drivers. The primary intervention was creating a PICU-ED Team (PET) and a checklist to guide the assessment and mitigation of risk for peri-intubation arrest and rapid consultation of the pediatric intensivists. The PET was iteratively refined, and we collected data by a video review of tracheal intubations. Results: Fifty-one patients with risk factors for peri-intubation arrest underwent tracheal -intubation in the PED from January 2016 to March 2020: 14 with PET activation since PET go-live in April 2019. None of the 14 PET patients had a peri-intubation cardiac arrest. Ninety-three percent (13/14) of PET patients were intubated in the PED, and 78% (10/13) of these patients had the first intubation attempt completed by PED physicians (balancing measures). Conclusion: We successfully developed the PET to mitigate the risk of peri-intubation cardiac arrest without significantly reducing key procedural opportunities for the PED. Initial data are promising, but further refinement is needed.